MANAJEMEN KURIKULUM BAHASA ARAB DI MADRASAH ALIYAH NORMAL ISLAM PUTERA RAKHA AMUNTAI - Alfianor, Alfianor (STIQ Amuntai, 2022)
The curriculum is an essential component of the education program. Therefore, curriculum management dramatically influences the success of learning activities. This study aims to exploit the direction of the Arabic language curriculum at MA NIPA Rakha Amuntai. This study uses qualitative methods, observation techniques, documentation, and interviews as a tool to explore data. At the same time, the analysis uses the theory of Miles and Huberman, namely data reduction, data display, and data verification. The results of this study are that MA NIPA Rakha Amuntai has its characteristics in managing the Arabic curriculum, namely by dividing it into several subjects. Moreover, these subjects are a branch or part of the Arabic language. Furthermore, with the Arabic language curriculum management, MA NIPA Rakha graduate students can compete in both State Universities in Indonesia and Universities in the Middle East such as Egypt, Yemen, Morocco, Tunis, Sudan, and Saudi Arabia. Moreover, almost every year MA NIPA Rakha sends its students to continue their studies in the Middle East. Therefore, theoretically and practically, this research is expected to add to the treasures of Islamic scholarship, especially about how to manage the Arabic language curriculum. In addition, this research is also likely to contribute to every educational institution to pay more attention to the management of the Arabic language curriculum that is good and follows the needs of students.